Dual Effect of Exogenous Nitric Oxide on Neuronal Excitability in Rat Substantia Gelatinosa Neurons - A-Reum Park; Hae In Lee; Dejidnorov Semjid; Do Kyung Kim; Sang Woo Chun (Neural Plasticity)
Nitric oxide (NO) is an important signaling molecule involved in nociceptive transmission. It can induce analgesic and hyperalgesic effects in the central nervous system. In this study, patch-clamp recording was used to investigate the effect of NO on neuronal excitability in substantia gelatinosa (SG) neurons of the spinal cord. Different concentrations of sodium nitroprusside (SNP; NO donor) induced a dual effect on the excitability of neuronal membrane: 1 mM of SNP evoked membrane hyperpolarization and an outward current, whereas 10 µM induced depolarization of the membrane and an inward current. These effects were prevented by hemoglobin and 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide potassium salt (c-PTIO) (NO scavengers), phenyl N-tert-butylnitrone (PBN; nonspecific reactive oxygen species scavenger), and through inhibition of soluble guanylyl cyclase (sGC). Pretreatment with n-ethylmaleimide (NEM; thiol-alkylating agent) also decreased effects of both 1 mM and 10 µM SNP, suggesting that these responses were mediated by direct S-nitrosylation. Charybdotoxin (CTX) and tetraethylammonium (TEA) (large-conductance Ca2+-activated K+ channel blockers) and glybenclamide (ATP-sensitive K+ channel blocker) decreased SNP-induced hyperpolarization. La3+ (nonspecific cation channel blocker), but not Cs+ (hyperpolarization-activated K+ channel blocker), blocked SNP-induced membrane depolarization. In conclusion, NO dually affects neuronal excitability in a concentration-dependent manner via modification of various K+ channels.